FLC based on static var compensator for power system transient stability enhancement - Mojeebalrhman M. A. Hassan; Xiuyun Sun; Abdelrahim Ate (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Transient Stability is the capability of a system to be able to return to its normal state after experiencing large disturbances. The static var compensator (SVC) is a shunt device of the flexible AC transmission systems (FACTS) family using power electronics to improve transient stability in power system. For the SVC control, it is usually used a PI controller, although PI controller is simpler and cheaper but not suitable when power system is subjected to transient stability since power system become non-linear system. In order to overcome this problem, the PI controller combined with Fuzzy controller is designed. Two types of faults were considered for this study to examine the effect of the fuzzy-SVC controller on system transient stability, the proposed fault types are single line to ground fault and three lines to ground fault. The performance and behavior of the designed fuzzy controller compared with that of the conventional PI controller in term of terminal voltage, rotor angle, and transmission line active power.